MODIFIKASI HURDLE TECHNOLOGY DENGAN PENAMBAHAN EKSTRAK KUNYIT DAN PENYIMPANAN SUHU DINGIN PADA INDUSTRI RUMAH TANGGA MIE BASAH - Giyarto Giyarto; Yuli Witono; Nany Mariah Qibthiyah (JURNAL AGROTEKNOLOGI, 2011)
Wet noodle is a popular food in Indonesia, which is widely produced by the small medium enterprises. This product has high water content, so that it is easy spoiled. The shelf life of wet noodle could extended by using the chemical preservative food agents. However, the application of these compounds are often occur misuses or malpractices. The safe and feasible treatments can be develop on the wet noodle producton is hurdle technology, that could be done with addition of natural antimicrobial compounds and physically treatment, like chilling. The research aim is to study the effect of hurdle technology modification on wet noodles quality and its economic feasibility in the home industry scales. The modification of hurdles were inserted the turmeric extract 3% and cold storage hurdle treatments on wet noodles production. The economic feasibility was identified using B/C ratio value, comparing with control (without insertion of hurdle technology). The research showed that the hurdle technology modification increased wet noodle quality and extended the shelf life of wet noodle. The wet noodle quality characteristics were total microbes 5,05 log cicles cfu/g, protein content 36%, TVB value 0,0024%, water content 55,51%, Aw 0,96, pH value 6,43, whiteness value 64. The wet noodles could be stored and safe until 96 hours, and the hurdle technology modification increased its economic feasibility caused the B/C ratio of 1,002. Keywords: wet noodle, hurdle technology modification, turmeric extract, economic feasibility